Identification of Mitoxantrone as a TRAIL-sensitizing agent for Glioblastoma Multiforme. Issue 5 (3rd May 2016) - Senbabaoglu, Filiz; Cingoz, Ahmet; Kaya, Ezgi; Kazancioglu, Selena; Lack, Nathan A.; Acilan, Ceyda; Bagci-Onder, Tugba
ABSTRACT: Tumor necrosis factor related apoptosis-inducing ligand (TRAIL) has tremendous promise in treating various forms of cancers. However, many cancer cells exhibit or develop resistance to TRAIL. Interestingly, many studies have identified several secondary agents that can overcome TRAIL resistance. To expand on these studies, we conducted an extensive drug-re-profiling screen to identify FDA-approved compounds that can be used clinically as TRAIL-sensitizing agents in a very malignant type of brain cancer, Glioblastoma Multiforme (GBM). Using selected isogenic GBM cell pairs with differential levels of TRAIL sensitivity, we revealed 26 TRAIL-sensitizing compounds, 13 of which were effective as single agents. Cardiac glycosides constituted a large group of TRAIL-sensitizing compounds, and they were also effective on GBM cells as single agents. We then explored a second class of TRAIL-sensitizing drugs, which were enhancers of TRAIL response without any effect on their own. One such drug, Mitoxantrone, a DNA-damaging agent, did not cause toxicity to non-malignant cells at the doses that synergized with TRAIL on tumor cells. We investigated the downstream changes in apoptosis pathway components upon Mitoxantrone treatment, and observed that Death Receptors (DR4 and DR5) expression was upregulated, and pro-apoptotic and anti-apoptotic gene expression patterns were altered in favor of apoptosis. Together, our results suggest that combination of Mitoxantrone and TRAIL can be a promising therapeutic approach for GBM patients.